Greek Words and Myth in Propertius 1.20 - Leo C. Curran (Greek, Roman, and Byzantine Studies, 2002)
<!--StartFragment--> The poem expoits the phonology of Greek, and particularly the name Hylas, to invoke dominant features of the myth, especially woodlands and water. <!--EndFragment-->